Studies from the anthropological laboratory, the anatomy school, Cambridge - Duckworth, W. L. H. (Wynfrid Laurence Henry), 1870-1956.; University of Cambridge. Anatomical Museum. (Cambridge, University press, 1904)
Short list of references with most of the chapters. On crania of Eskimo in the University Museum (p. [181]-183) -- A contribution to Eskimo craniology (with the assistance from B.H. Pain) (p.[184]-[202]) -- An account of some Eskimo from Labrador ([268]-273). Mode of access: Internet.